Pengaruh Penggunaan Media Audio Visual terhadap Keterampilan Menulis Fabel Kelas VII UPT SPF SMPN 48 Makassar - Nur Rahma Khairunnisa; Aliem Bahri; Haslinda Haslinda (Journal on Education, 2023)
This study aims to improve the learning outcomes of writing fables by using audio-visual media in class VII students of UPT SPF SMPN 48 Makassar. This type of research is quantitative research with pre-experimental methods, the research design used is one group pretest-posttest involving one class which is held in two meetings. The procedure of this research includes preparation, implementation, and completion. The subjects in this study were 36 students of class VII UPT SPF SMPN 48 Makassar. The results of research and analysis of statistical data can be seen that the average values ​​of the Pretest and Posttest using audio-visual media in learning to write fables are 54 and 82.05. Furthermore, inferential statistical analysis on the t-test results obtained that thirung is 8.873 and ttable is 1.689 at a significant level of 0.05 or 5% so tcount (8.873) > ttable (1.689) stated that H0 is rejected and H1 is accepted then the hypothesis is accepted. In the N-Gain test, it can be analyzed that the ability of students' learning outcomes to write fables using audio-visual media at intervals of g ≥ 0.7 is in the high category. Based on the results of the research above, it can be concluded that learning outcomes have an effect on the use of audio-visual media on fable writing skills for class VII UPT SPF SMPN 48 Makassar.